PTEN enhances the radiosensitivity of melanoma by inhibiting DNA-PKcs - Zhu, Shengqian; Xu, Haitao; Shen, Fu; Chen, Fangying; Wang, Yangjian (Frontiers in Cell and Developmental Biology, 2026)
BackgroundThe phosphatase and tensin homolog (PTEN) is a classical tumor-suppressor gene. Its expression deficiency concurrently drives disease progression in approximately 30% of melanomas and is closely associated with radiotherapy tolerance. However, there is a lack of systematic evidence regarding whether and how PTEN regulates the radiosensitivity of melanoma.MethodsThe expression of PTEN was validated using TCGA database, clinical tissue microarrays, and multiple melanoma cell lines. PTEN knockdown (PTEN-KD) and PTEN overexpression (PTEN-OE) stable cell lines were constructed using lentiviral vectors. CCK-8, colony formation assay, annexin V/PI flow cytometry, neutral comet assay, cell-cycle analysis, and Western blotting were used to assess the biological changes in cells after 0 Gy–8 Gy γ-ray irradiation (IR). A cell-derived xenograft model was established, and the tumor volume was observed after local 10 Gy IR for 28 days; in addition, H&E, Ki67, and TUNEL evaluations were performed.ResultsThe expression of PTEN in melanoma tissues and cell lines was significantly lower than that in normal controls. IR could induce a transient upregulation of PTEN followed by rapid downregulation. PTEN-OE significantly inhibited proliferation, reduced the clone survival rate, increased apoptosis, and weakened radiation-induced G2/M phase arrest; however, the opposite was true for PTEN-KD. Mechanistically, PTEN-OE inhibited the DNA-PKcs axis, reduced NHEJ-mediated rapid repair, and increased the persistent expression of γ-H2AX. PTEN-KD activated the p-ATM/p-Chk2 signaling. Animal experiments confirmed that the tumor volume in the PTEN-OE + IR group was significantly lower than that in the NC + IR group, with an expanded necrotic area, a decreased Ki67 index, and an increased TUNEL-positive rate.ConclusionPTEN enhances the radiosensitivity of melanoma by inhibiting the DNA-PKcs signal, weakening NHEJ repair, and delaying cell-cycle recovery. PTEN can serve as a biomarker for radiotherapy response prediction and a target for sensitization intervention, providing an experimental basis for precise radiotherapy strategies for melanoma.